Diversity of tree communities in Mount Patuha region, West Java (Biodiversitas Journal of Biological Diversity, 2009)
Junaedi DI, Mutaqien Z (2010) Diversity of tree communities in Mount Patuha region, West Java. Biodiversitas 11: 75-81. Treevegetation analysis was conducted in three locations of Mount Patuha region, i.e. Cimanggu Recreational Park, Mount Masigit Protected Forest, and Patengan Natural Reserve. Similarity of tree communities in those three areas was analyzed. Quadrant method was used to collect vegetation data. Morisita Similarity index was applied to measure the similarity of tree communities within three areas. The three areas were dominated by Castanopsis javanica A. DC., Lithocarpus pallidus (Blume) Rehder and Schima wallichii Choisy. The similarity tree communities were concluded from relatively high value of Similarity Index between three areas. Cimanggu RP, Mount Masigit and Patengan NR had high diversity of tree species. The existence of the forest in those three areas was needed to be sustained. The tree communities data was useful for further considerations of conservation area management around Mount Patuha.Key words: Mount Patuha, tree communities, plant ecology, remnant forest